Direct electroplating of Ag nanowires using superionic conductors. Issue 1 (19th August 2019) - Guo, Zeliang; Zhao, Yusen; Sun, Shipeng; Wu, Hui
Abstract : Solid electrolytes can be applied in the metal electrodeposition industry. Abstract : Solid electrolytes can be applied in the metal electrodeposition industry. We propose a new strategy for fabricating Ag and Cu nanowire arrays by direct all-solid electroplating. The Ag nanowires are uniformly aligned and have a controllable length ranging between 2 μm and 300 μm. Moreover, the Ag nanowires show uniform lattice orientation on a large scale. By designing and altering the pattern of the electrolyte surface, the plated layer shows the corresponding patterns. This new electroplating strategy provides new insights to metal nanowire growth and patterned coating designs that are simple, inexpensive and versatile.